Baicalein Ameliorates Myocardial Ischemia Through Reduction of Oxidative Stress, Inflammation and Apoptosis via TLR4/MyD88/MAPKS/NF-κB Pathway and Regulation of Ca2+ Homeostasis by L-type Ca2+ Channels - Li, Jinghan; Yang, Yakun; Wang, Hua; Ma, Donglai; Wang, Hongfang; Chu, Li; Zhang, Yuanyuan; Gao, Yonggang (Frontiers in Pharmacology, 2022)
Background: Baicalein (Bai) is the principal ingredient of Scutellaria baicalensis Georgi. Reports concerning the therapeutic advantages in treating cardiovascular diseases have been published. However, its protective mechanism towards myocardial ischemia (MI) is undefined. Objective: The aim of this study was to investigate the protective mechanisms of Bai on mouse and rat models of MI. Methods: Mice were pre-treated with Bai (30 and 60 mg/kg/day) for seven days followed by subcutaneous injections of isoproterenol (ISO, 85 mg/kg/day) for two days to establish the MI model. Electrocardiograms were recorded and serum was used to detect creatine kinase (CK), lactate dehydrogenase (LDH), superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and malondialdehyde (MDA). Cardiac tissues were used to detect Ca2+ concentration, morphological pathologies, reactive oxygen species (ROS), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). In addition, the expression levels of Bcl-2-associated X (Bax), B cell lymphoma-2 (Bcl-2), Caspase-3, Toll-like receptor-4 (TLR4), myeloid differentiation protein 88 (MyD88), nuclear factor-kappa B (NF-κB), p-p38, p-extracellular signal-regulated kinase1/2 (p-ERK1/2) and c-Jun N-terminal kinase (p-JNK) were assessed by western blots in myocardial tissues. The effects of Bai on L-type Ca2+ currents (ICa-L), contractility and Ca2+ transients in rat isolated cardiomyocytes were monitored by using patch clamp technique and IonOptix system. Moreover, ISO-induced H9c2 myocardial injury was used to detect levels of inflammation and apoptosis. Results: Bai caused an improvement in heart rate, ST-segment and heart coefficients. Moreover, Bai led to a reduction in CK, LDH and Ca2+ concentrations and improved morphological pathologies. Bai inhibited ROS generation and reinstated SOD, CAT and GSH activities in addition to inhibition of replenishing MDA content. Also, expressions of IL-6 and TNF-α in addition to Bax and Caspase-3 were suppressed, while Bcl-2 expression was upregulated. Bai inhibited protein expressions of TLR4/MyD88/MAPKS/NF-κB and significantly inhibited ICa-L, myocyte contraction and Ca2+ transients. Furthermore, Bai caused a reduction in inflammation and apoptosis in H9c2 cells. Conclusions: Bai demonstrated ameliorative actions towards MI, which might have been related to attenuation of oxidative stress, inflammation and apoptosis via suppression of TLR4/MyD88/MAPKS/NF-κB pathway and adjustment of Ca2+ homeostasis via L-type Ca2+ channels.